2013
DOI: 10.1021/jp4016646
|View full text |Cite
|
Sign up to set email alerts
|

Cation Effects on Rotational Dynamics of Anions and Water Molecules in Alkali (Li+, Na+, K+, Cs+) Thiocyanate (SCN) Aqueous Solutions

Abstract: Waiting time dependent rotational anisotropies of SCN − anions and water molecules in alkali thiocyanate (XSCN, X = Li, Na, K, Cs) aqueous solutions at various concentrations were measured with ultrafast infrared spectroscopy. It was found that cations can significantly affect the reorientational motions of both water molecules and SCN − anions. The dynamics are slower in a solution with a smaller cation. The reorientational time constants follow the order of Li + > Na + > K + ≃ Cs + . The changes of rotationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
135
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 66 publications
(151 citation statements)
references
References 50 publications
15
135
0
1
Order By: Relevance
“…A similar fsIR experimental set up was used for a group of alkali thiocyanate solutions with a series of concentrations up to 15 M, 47 with the discussion focusing on how ion clustering, at high concentrations (>5 M), leads to segregation of the rotational dynamics between water and anions. A ps amplifier and a fs amplifier were synchronized with the same seed pulse from a 82 MHz oscillator.…”
Section: Methodsmentioning
confidence: 99%
“…A similar fsIR experimental set up was used for a group of alkali thiocyanate solutions with a series of concentrations up to 15 M, 47 with the discussion focusing on how ion clustering, at high concentrations (>5 M), leads to segregation of the rotational dynamics between water and anions. A ps amplifier and a fs amplifier were synchronized with the same seed pulse from a 82 MHz oscillator.…”
Section: Methodsmentioning
confidence: 99%
“…The experimental setup for the ultrafast IR spectroscopy has been described elsewhere. 39,41,44,45 Briey, a ps amplier and a fs amplier are independently operated and synchronized with the same seed pulse from a Ti-sapphire oscillator. The ps amplier pumps an OPA to produce $1 ps Mid-IR pulses with a bandwidth $18 cm À1 at 1 kHz repetition rate.…”
Section: Methodsmentioning
confidence: 99%
“…39,40 We found that ions form significant amount of clusters in KSCN aqueous solutions. [41][42][43][44] We further investigated the different behavior of rotational dynamics of water molecules and anions due to the structural inhomogeneity and discussed the anion and cation effects. 43,44 To investigate the specic cation effect on the water dynamics in electrolyte aqueous solution, it is necessary to separate the contribution from dynamics of water in anionic hydration shell and water dynamics in the bulk liquid.…”
Section: Introductionmentioning
confidence: 99%
“…However, as the author pointed out, the two dimensional Infrared (2D IR) spectroscopy with access to all vibrational modes is needed for the comprehensive analysis of vibrational energy relaxation in monomeric water. In our previous studies, we developed the modespecific vibrational energy transfer method based on the 2D IR spectroscopy and successfully applied this method to the electrolyte aqueous solution systems [31][32][33][34][35][36]. Following the experimental and data analysis procedures established in our previous reports, we investigated the vibrational relaxation dynamics of monomeric water molecule dissolved in d-chloroform solution using the 2D IR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%